Environmentally Friendly Utilization of Wheat Straw Ash in Cement-Based Composites - Memon, Shazim Ali; Wahid, Israr; Khan, Muhammad Khizar; Tanoli, Muhammad Ashraf; Bimaganbetova, Madina (MDPI, 2018)
The open burning of biomass residue constitutes a major portion of biomass burning and leads to air pollution, smog, and health hazards. Various alternatives have been suggested for open burning of crop residue; however, each of them has few inherent drawbacks. This research suggests an alternative method to dispose wheat straw, i.e., to calcine it in a controlled environment and use the resulting ash as a replacement of cement by some percentage in cement-based composites. When wheat straw, an agricultural product, is burned, it is very rich in SiO2, which has a pozzolanic character. However, the pozzolanic character is sensitive to calcination temperature and grinding conditions. According to the authors’ best knowledge, until now, no systematic study has been devised to assess the most favorable conditions of burning and grinding for pozzolanic activity of wheat straw ash (WSA). Hence, a systematic experimental program was designed. In Phase I, calcination of WS was carried out at 500 ◦C, 600 ◦C, 700 ◦C, and 800 ◦C for 2 h. The resulting ashes were tested for color change, weight loss, XRD, XRF, Chapelle activity, Fratini, and pozzolanic activity index (PAI) tests. From test results, it was found that beyond 600 ◦C, the amorphous silica transformed into crystalline silica. The WSA calcined at 600 ◦C was found to satisfy Chapelle and Fratini tests requirements, as well as the PAI requirement of ASTM at 28 days. Therefore, WSA produced at 600 ◦C (WSA600) showed the best pozzolanic performance. In Phase II, WSA600 was ground for various intervals (15–240 min). These ground ashes were tested for SEM, Blaine fineness, Chapelle activity, Fratini, and PAI tests. From test results, it was observed that after 120 min of grinding, there was an increase of 48% in Blaine surface area, with a consequence that WSA-replaced cement cubes achieved a compressive strength almost similar to that of the control mix. Conclusively, wheat straw calcined at 600 ◦C and ground for 120 min was found to be the most effective way to use pozzolanic material in cement-based composites. The addition of WSA in cement-based composites would achieve manifold objectives, i.e., aiding in the production of environmentally friendly concrete, the use of wheat straw as fuel for electricity production, and adding economic value to wheat straw.
Keywords: wheat straw ash; pozzolanic activity; cement; concrete; calcination; grinding; environmental friendly materials